Mutational Portrait of Lung Adenocarcinoma in Brazilian Patients: Past, Present, and Future of Molecular Profiling in the Clinic - Freitas, Helano C.; Torrezan, Giovana Tardin; Cunha, Isabela Werneck da; Macedo, Mariana Petaccia; Karen de Sá, Vanessa; Corassa, Marcelo; Ferreira, Elisa Napolitano e; Saito, Augusto Obuti; Dal Molin, Graziela Zibetti; Cordeiro de Lima, Vladmir C.; Carraro, Dirce Maria (Frontiers in Oncology, 2020)
Objectives: Approximately 60% of lung adenocarcinomas (LAs) carry mutations that can guide treatment with tyrosine-kinase inhibitors (TKI) and other targeted therapies. Data on activating mutations in EGFR and other tyrosine-kinase receptor (TKR) genes in highly admixed populations, such as that of Brazil, are scarce. In this study, we comprehensively analyzed the actionable alteration profile of LA in Brazilian patients. Materials and Methods:EGFR driver mutation data were collected from a large Brazilian LA cohort covering an 8-year period of molecular testing in a single institution. Tests were performed using three distinct methods, and demographic and histopathological data were analyzed. For a subset of patients, driver mutations in KRAS, NRAS, and BRAF and gene fusions involving TKR genes (before TKI treatment) and EGFR T790M (after TKI treatment) were assessed. Results:EGFR mutations were detected in 25% of 1,316 LAs evaluated, with exon 19 deletions and exon 21 L858R TKI sensitizing mutations representing 72.5% of all mutations. Mutation rates were higher in women and non-smokers (p < 0.001). Next-generation sequencing was very sensitive, with a lower rate of inconclusive results compared with Sanger sequencing and pyrosequencing. EGFR/RAS/BRAF hotspot gene panels were applied in 495 LA cases and detected oncogenic mutations in 51.3% of samples, most frequently in EGFR (22.4%) and KRAS (26.9%). In subgroups of 36 and 35 patients, gene fusions were detected in 11.1% of tumors and EGFR T790M resistance mutations were detected in 59% of plasma samples from patients previously treated with TKI, respectively. Conclusion: This report provides the first comprehensive actionable alteration portrait of LA in Brazil. The high rate of actionable alterations in EGFR and other driver genes in LA reinforces the need to incorporate TKI guided by molecular diagnostics into clinical routines for patients in both public and private healthcare systems.